2019
DOI: 10.1016/j.wasec.2019.100047
|View full text |Cite
|
Sign up to set email alerts
|

Water access transformations: Metrics, infrastructure, and inequities

Abstract: Scholarship on water insecurity has carried over an important insight from studies of food insecurity: Insecurity often occurs in the midst of plenty, and water insecurity is therefore better characterized by inaccessibility than by scarcity. Access to clean, adequate, and reliable water is, however, more challenging to systematize than access to food. Water is fluid and protean, and only when it is safely stored can people pretend to own it. In this paper, I make a case for the centrality of infrastructure -s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The presence of storage containers also determined the availability of water in the household. In investigating sources of water, as in other studies [10,25], it was discovered that a reliance on surface water, such as rivers and streams, was very common in the study area.…”
Section: Discussionmentioning
confidence: 56%
“…The presence of storage containers also determined the availability of water in the household. In investigating sources of water, as in other studies [10,25], it was discovered that a reliance on surface water, such as rivers and streams, was very common in the study area.…”
Section: Discussionmentioning
confidence: 56%
“…Stevenson et al (2016) initially could not offer specific reasons, but suggested that the water improvements might not have solved stressors of water governance (i.e., the stressor was not water itself, but how water was managed). Later work clarified that the water governance was indeed a stressor in this case, as a flat fee structure penalized poorer households and new opening/closing hours heightened the opportunity costs of using the water system (Stevenson, 2019).…”
Section: Mechanismsmentioning
confidence: 99%
“…Using a randomized encouragement design, they showed that connection to the water grid yielded significant increases in time gains, social integration, and quality of life while reducing conflicts about water-related problems within families and with neighbors. The second longitudinal study followed 223 rural Ethiopian women's psychological distress (on the SRQ-20) before and after a community water supply improvement project (Stevenson, 2019;Stevenson et al, 2016). Stevenson's team found that SRQ-20 scores showed no change before and after the intervention, even though water security measurably increased by more than half baseline standard deviation.…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations